2002
DOI: 10.1074/jbc.m201912200
|View full text |Cite
|
Sign up to set email alerts
|

The Donor Substrate Specificity of the Human β1,3-Glucuronosyltransferase I toward UDP-Glucuronic Acid Is Determined by Two Crucial Histidine and Arginine Residues

Abstract: The human ␤1,3-glucuronosyltransferase I (GlcAT-I) plays a key role in proteoglycan biosynthesis by catalyzing the transfer of glucuronic acid onto the trisaccharide-protein linkage structure Gal␤1,3Gal␤1,4Xyl␤-O-Ser, a prerequisite step for polymerization of glycosaminoglycan chains. In this study, we identified His 308 and Arg 277 residues as essential determinants for the donor substrate (UDP-glucuronic acid) selectivity of the human GlcAT-I. Analysis of the UDP-glucuronic acid-binding site by computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…Similar results have been obtained from other GTs (Qasba et al, 2005). Nevertheless, no conserved amino acid residues have been identified as general determinants of sugar specificity (Ouzzine et al, 2002;Kubo et al, 2004;Modolo et al, 2007;Yonekura-Sakakibara et al, 2007).…”
supporting
confidence: 73%
“…Similar results have been obtained from other GTs (Qasba et al, 2005). Nevertheless, no conserved amino acid residues have been identified as general determinants of sugar specificity (Ouzzine et al, 2002;Kubo et al, 2004;Modolo et al, 2007;Yonekura-Sakakibara et al, 2007).…”
supporting
confidence: 73%
“…The x-ray structure of the mutant showed that there was sufficient room for the enzyme to accommodate the N-acetyl group of the alternate donor. For ␤1-3-glucuronosyltransferase, mutation of histidine 308 to arginine produces an enzyme that can efficiently utilize UDP-Glc, UDP-Man, and UDP-GlcNAc as well as UDP-GlcA donor (21). However, unlike these examples of broadened donor specificity, the P234S mutation in glycosyltransferase B results in a complete reversal of donor saccharide recognition.…”
Section: Table Imentioning
confidence: 97%
“…GlcAT-I has received much attention because it plays a central role at a branching point common to various GAG chains, and it has been suggested to be rate-limiting in GAG synthesis in Chinese hamster ovary cells (18). We have been deeply involved in structural and functional studies of human GlcAT-I (19)(20)(21). We recently reported that IL-1␤ down-regulates GlcAT-I expression and activity and suggested that this may contribute to the reduced biosynthesis of GAGs observed in chondrocytes after IL-1␤ treatment (22).…”
mentioning
confidence: 99%